PREVALENCE OF RISK FOR DEMENTIA AND IT’S RELATIONSHIP TO PHYSICAL ACTIVITY - Sabri, Rika (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
As seen in the field, there are still many elderly who have dementia risk status. Recognizing the factors associated with dementia is the proper treatment to reduce the risk of dementia in the elderly. One of the preventive efforts that can be done by the elderly is to do physical activity. This study was conducted to determine whether there is a relationship between the level of physical activity and the risk of dementia in the elderly at the Andalas Public Health Center, Padang City, in 2021. This type of research is quantitative with an analytic design and a cross-sectional approach. The sampling technique used is purposive sampling approach with a total sample of 104 respondents. The research instruments used were the Global Physical Activity Questionnaire (GPAQ) and the Mini-Mental State Examination (MMSE). Data analysis using Chi-Square test. The results showed that most (51.0%) of the respondents had moderate physical activity levels, and most (51.9%) of the elderly were at risk of developing dementia. There is a significant relationship between the physical activity level with the risk of dementia in the elderly, where the value of p 0.001. It is recommended that the Puskesmas provide education related to preventing the risk of dementia in the elderly, especially by carrying out physical activities determined by the Puskesmas (Public Health Center) according to the condition of the elderly Andalas Health Center work area, Padang City.